Celebrating 30 years of Feminism & Psychology. (August 2021) - Macleod, Catriona Ida; Capdevila, Rose; Marecek, Jeanne; Braun, Virginia; Gavey, Nicola; Wilkinson, Sue
Feminism & Psychology ( F&P ) was launched in 1991 with a sense of possibility, enthusiasm and excitement as well as a sense of urgent need – to critique and reconstruct mainstream psychology (theory, research methods, and clinical practice). Thirty years have now passed since the first issue was produced. Thirty volumes with three or four issues have been published each year, thanks to the efforts of many. On the occasion of F&P 's 30th anniversary, we, the present and past editors, reflect on successes, changes and challenges in relation to the journal. We celebrate the prestigious awards accruing to the journal, its editors, and authors, and the significant contributions the journal has made to critical feminist scholarship at the interface of feminisms and psychologies. We note some of the theoretical and methodological developments and social changes witnessed over the last three decades. We highlight challenges facing feminist researchers in academia as well as international feminist publishing. We conclude that the initial enthusiasm and excitement expressed by the then editorial collective was justified. But, there is still much work to be done.